Efforts To Increase Understanding in Stroke Patients About Range of Motion Exercises - Septiyana Achmad, Viyan; A. Sasarari, Zusana; Yunus, Muh (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Efforts to increase understanding in stroke patients about range of motion exercises have an important role in optimizing the rehabilitation process and their quality of life. Evidence-based educational approaches are emphasized as the main foundation, where accurate and research-based information is conveyed to patients. Community empowerment was also reviewed, highlighting the importance of involving communities and families in supporting patients in running exercise programs. The implementation of community service activities in the form of counseling efforts to provide understanding for the community about range exercises using demonstrations and role play. The results showed that there was an increase in public understanding of the provision of range of motion training for stroke patients. It can be concluded that efforts to increase understanding in stroke patients about range of motion exercise have a crucial role in the rehabilitation process and improve their quality of life. Through evidence-based education, community empowerment, and continuous monitoring and evaluation, we can achieve positive outcomes.